Limited Capacity or Involvement of Excision Repair, Double-Strand Breaks, or Translesion Synthesis for Psoralen Cross-Link Repair in Escherichia coli. Issue 1 (25th July 2018) - Cole, Jessica M; Acott, Jedidiah D; Courcelle, Charmain T; Courcelle, Justin
Abstract: DNA interstrand cross-links are complex lesions that covalently bind complementary strands of DNA and whose mechanism of repair remains poorly understood. In Escherichia coli, several gene products have been proposed to be involved in cross-link repair based on the hypersensitivity of mutants to cross-linking agents. However, cross-linking agents induce several forms of DNA damage, making it challenging to attribute mutant hypersensitivity specifically to interstrand cross-links. To address this, we compared the survival of UVA-irradiated repair mutants in the presence of 8-methoxypsoralen—which forms interstrand cross-links and monoadducts—to that of angelicin—a congener forming only monoadducts. We show that incision by nucleotide excision repair is not required for resistance to interstrand cross-links. In addition, neither RecN nor DNA polymerases II, IV, or V is required for interstrand cross-link survival, arguing against models that involve critical roles for double-strand break repair or translesion synthesis in the repair process. Finally, estimates based on Southern analysis of DNA fragments in alkali agarose gels indicate that lethality occurs in wild-type cells at doses producing as few as one to two interstrand cross-links per genome. These observations suggest that E. coli may lack an efficient repair mechanism for this form of damage.